Impact of Verigene Multiplex PCR for Positive Blood Cultures and Gram-negative Bacteremia. (4th October 2017) - Adams, Matthew; Nix, David; Matthias, Kathryn; Althaghfi, Abdulhmid; Bach, Mimi; Al Mohajer, Mayar
Abstract: Background: Many patients with bacteremia due to Gram-negative organisms are not treated appropriately. This has been linked to high rates of multi-drug resistant organisms, hospital costs, length of stay, and mortality. The purpose of this study was to assess the effect of implementation of Verigene multiplex PCR on appropriate use of antibiotics, and the time to streamlining of therapy in this population. Methods: This study included hospitalized patients with Gram-negative organisms isolated from blood cultures both six months before, and six months after the implementation of Verigene at a tertiary care academic medical center. An institutional review board approved this study. We excluded patients that had organisms isolated from autopsy sample and patients under the age of 18. Appropriate therapy was defined as any antibiotic therapy to which the organism was reported as being susceptible once susceptibility results were available. Streamlined therapy was defined as the narrowest antibiotic selection based off organism susceptibility. The primary outcome measure was the time to streamlining of therapy (before culture and susceptibility date were available). Data was compared by group (before and after Verigene implementation) using multiple logistic regression model in SAS. Results: A total of 287 patients were included. 140 of the subjects were male (48.8%). Mean age in the pre-verigene group was 61.5 years (SD 17.1) and the mean age in the post-verigene group was 59.7 (SD 18.2). In 93 patients, cultures were collected in the ICU setting (32.4%). In nine post-verigene patients, ESBL with the CTX-M resistance marker was isolated. Six of these patients were switched from inappropriate therapy to a carbapenem. The time to appropriate antibiotics in the pre-verigene group was 0.4 days (SD 0.8) and in the post-verigene group 0.4 days (SD 1.0 P = 0.57). The time to streamlining of antibiotics following culture was improved in the post-verigene group (1.9 days, SD 1.3) compared with the pre-verigene group (2.6 days, SD 1.4 P = 0.01). Conclusion: The use of Verigene multiplex PCR was associated with improved time to streamlining of antibiotic therapy in patients with Gram-negative bacteremia. Disclosures: All authors: No reported disclosures.